2016
DOI: 10.4103/0301-4738.194336
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations of Type 1 diabetes mellitus in pediatric population

Abstract: Context:To evaluate the necessity of ocular screening in Type 1 diabetes mellitus (DM).Aims:This study aims to investigate the diabetes-related ocular changes according to the glycosylated hemoglobin (HbA1c) level and duration of diabetes in children and compare the results with nondiabetic healthy children.Settings and Design:Observational cross-sectional study designed by ophthalmology and pediatric endocrinology clinics.Subjects and Methods:Forty-two children with Type 1 DM, 42 healthy gender- and age-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 29 publications
(39 reference statements)
7
22
1
Order By: Relevance
“…Previous studies revealed alterations in the macular thickness measurements of type 1 or type 2 diabetic patients with and without DR. [14][15][16] However, only the children with well-controlled type 1 DM who had full visual acuity in both eyes and no sign of DR after a fundoscopic examination and fundus photographs were included in our study. Akil et al 17 investigated the alterations in the anterior and posterior segment findings of children with type 1 DM with and without DR and found that the measurements of total macular volume and central retinal thickness were significantly lower in the diabetic group than in controls. Van Dijk et al 18 investigated which retinal layers are most affected by diabetes in patients with type 1 DM who have no or minimal DR and demonstrated that thinning occurs in inner retinal layers, particularly the ganglion cell layer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed alterations in the macular thickness measurements of type 1 or type 2 diabetic patients with and without DR. [14][15][16] However, only the children with well-controlled type 1 DM who had full visual acuity in both eyes and no sign of DR after a fundoscopic examination and fundus photographs were included in our study. Akil et al 17 investigated the alterations in the anterior and posterior segment findings of children with type 1 DM with and without DR and found that the measurements of total macular volume and central retinal thickness were significantly lower in the diabetic group than in controls. Van Dijk et al 18 investigated which retinal layers are most affected by diabetes in patients with type 1 DM who have no or minimal DR and demonstrated that thinning occurs in inner retinal layers, particularly the ganglion cell layer.…”
Section: Discussionmentioning
confidence: 99%
“…In children, frequent screening should be recommended for neuropathy related complications such as dry eye syndrome, glaucoma and diabetic retinopathy in Type1 diabetes mellitus. This is because a longer duration of diabetes can cause microvascular involvement and long term follow up is also required [15]. Inflammation can…”
Section: Discussionmentioning
confidence: 99%
“…Positive patients showed significant trend with both enhancing age and duration of DM (Table 2) with no significant statistical difference between the two groups (data not shown). Age (years) 30-39 0 (0) 0.005 0 (0) 0.01 0 (0) < 0.001 0 (0) 0.007 40-49 0 (0) 0 (0) 0 (0) 0 (0) 16,[23][24][25][26] However, to the best of our knowledge, no study till date has tried to compare the prevalence of dry eye syndrome between patients of Type 1 and Type 2 diabetes, especially with focus on the Eastern-Indian population.…”
Section: Rose Bengal Dye Staining Followed By Van Bijsterveld Scorinmentioning
confidence: 99%